PENGEMBANGAN UMKM SPIRULINABATAM.ID MELALUI MEDIA SOSIAL DAN ANALISA KONSUMEN - Putra, Edy Yulianto; Fahlevi, Renza; Fidia; Macnico, Peter; Willam (PORTAL RISET DAN INOVASI PENGABDIAN MASYARAKAT, 2022)
Spirulinabatam.Id is a digital MSME engaged in organic health and beauty. The purpose of this research is to analyze segmentation and consumer data on the development of Spirulinabatam.Id MSMEs. This study used observation and survey methods in the form of a questionnaire. Data obtained from interviews with Spirulinabatam.Id partners and questionnaires were distributed online via social media. The respondents used were 42 people who were consumers or customers who had purchased at Spirulinabatam. The results after implementation indicated that Spirulinabatam.Id experienced considerable development with increased transactions made and an increase in new audiences and followers before and after implementation.